DESIGN OF THERMAL EQUIPMENT MILLING FOR FABRICATING THE TIO2 PHOTOCATALYSTS COATED GRAIN POLYMERS (Jurnal Pendidikan Fisika Indonesia, 2015)
Organic waste water treatment can be conducted with technique of photocatalytic. Photocatalytic activity involves factors light intensity and amount of catalyst. In order this process can take place optimally, the catalyst material coating on the surface of the material buffer such as polymer shaped grains can be an alternative method. Setting the temperature and the duration of heating automatically is very efficient in controlling the physical characteristics of the photocatalyst materials. In this experiment, modification done on of the two types of thermal equipment milling namely cylindrical equipment milling equipped with heater and equipment milling based electric oven. The testing process of the thermal equipment milling performed with controlled temperature in the range of 110 ° C and setting the timer to 60 minutes. In testing the thermal characteristics of milling equipment, it takes as long as 220 minutes for each immobilization process using cylindrical milling and 65 minutes when using an electric oven. Setting the temperature and time in the electric oven milling  can be performed automatically, which can not be performed using cylindrical milling. Milling equipment based electric oven has also been used in the selection of buffer polymer materials and fabricate TiO2 photocatalysts which tested on photodegradation of organic compound of methylene blue (MB).Penjernihan air limbah organik dapat dilakukan dengan teknik fotokatalisis. Agar aktivitas fotokatalitik yang melibatkan faktor intensitas cahaya dan jumlah katalis dapat berlangsung secara optimal, pelapisan material katalis pada permukaan material penyangga berupa bulir polimer termoplastik dapat menjadi salah satu alternatif. Pengaturan temperatur dan lamanya pemanasan secara otomatis sangat efisien dalam mengendalikan karakteristik fisis material fotokatalis Dalam penelitian ini dilakukan modifikasi terhadap dua jenis peralatan thermal millng, yaitu peralatan milling cylinder yang dilengkapi dengan komponen pemanas dan peralatan miling berbasis oven listrik. Proses pengujian milling dilakukan dengan temperatur terkontrol pada kisaran 110 °C dan pengaturan timer 60 menit. Dalam pengujiankarakteristik termal kedua alat tersebut, dibutuhkan waktu selama 220 menit untuk setiap proses imobilisasi menggunakan milling cylinder dan 65 menit bila menggunakan peralatan berbasis oven listrik. Pengaturan temperatur dan waktu pada alat berbasis oven listrik dapat dilakukan secara otomatis, yang tidak dapat dilakukan menggunak milling cylinder. Peralatan milling berbasis oven listrik ini juga telah digunakan dalam pemilihan polimer penyangga material fotokatalis TiO2 serta pabrikasi fotokatalis TiO2 yang diujikan dalam fotodegradasi senyawa organik metilen biru (MB).